BERSERI Organic Village in the Gang Balong Kediri City - Yani, Erna Rahma; Hardjito, Koekoeh; Suwoyo, Suwoyo (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2020)
This program aims to empower Ragam Kader in realizing a “Berseri” Organic Village in the Gang Balong Environment, Kediri City. The method is mentoring introspective surveys by kader, community deliberations, education and assistance in the implementation of a serial organic village. The activity assessment indicators include three components of the assessment, namely components of hygiene, health and independence. The results of this program showed that the people could use waste into organic fertilizer, the environment was cleaner, comfortable (100%). The people do not suffer from ARI, infectious diseases, or malnourished. The people willing to take care of the plant, no people stated that they were willing to take care of the plants or were going to increase the variety of the plants, all people stated that they were continuing to cultivate the plants, no people stated that they were increasing their income. The conclusion of the activity is that various cadres are able to actively participate in realizing the serial village, the community feels that the environment is cleaner, organic waste can be used and the environment becomes more comfortable. Suggestions need to be increased efforts to increase the variety of plant types and efforts to increase community income